The Characterisation of Fracture Resistance of Asphalt Mixtures Containing Rubber Modifiers and a Wax-Based Additive. (17th January 2023) - Poovaneshvaran, Sharvin; Mohd Hasan, Mohd Rosli; Jamshidi, Ali; Mohd Ghazali, Mohd Fahmi Haikal; Yang, Xu; Putra Jaya, Ramadhansyah
Abstract : Asphalt mixture modification with rubberised material frequently results in improved characteristics and extended service life in actual application. This research characterised the synergistic consequences of rubber modifiers (crumb rubber powder (CRP) and natural rubber latex (NRL)) and wax-based admixtures (Tough Fix Hyper (TFH)) on the performance of the asphalt mixture from the fracture energy and laboratory fracture resistance perspectives. Semicircular bending (SCB) and indirect tensile strength (ITS) tests were conducted to assess the fracture properties of the asphalt mixture samples. To prepare asphalt mixture samples, the wet method was utilised. Higher CRP levels resulted in greater strength and a longer time to attain peak force for both control and mixtures containing wax admixture, as determined by SCB. The interaction between the higher CRP or NRL content and the TFH additive enhanced the fracture resistance, indicating that the components are highly compatible. The 10L + TFH additive produced the highest fraction of energy, indicating a more significant improvement than the counterpart mixes containing the CRP modifier. In addition, incorporation of the CRP and NRL increased the fracture plastic zone (FPZ), resulting in increased fracture toughness. Therefore, the gradient of fracture toughness and fracture energy in the asphalt mix depends on the rubber type, content, and TFH. Although the higher CRP, NRL, and TFH improve the fracture energy and cracking resistance, they increase the crack initiation and propagation velocities, whereby the high bitumen stiffness makes the mixture more brittle than the control mixture. Caution should be exercised when selecting the content of rubber modifier and TFH for the asphalt pavements in low-temperature service. Also, there is a direct interconnection between fracture resistance and fracture energy in the mixtures containing CRP, NRL, and TFH. Such correlations can be used as the premise of predictive micro- and macro-models to evaluate mixture performance in terms of fracture resistance.